2009
DOI: 10.1096/fasebj.23.1_supplement.955.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Reduces Prostate Carcinogenesis in a Transgenic Model

Abstract: Several epidemiological studies have reported an inverse association between physical activity and the risk of prostate cancer. In general, as exercise intensity increased in the rats/mice, the likelihood that physical activity inhibited carcinogenesis increased. In order to establish an animal model to investigate the effects of physical activity on prostate cancer development, the present study used C3(1)Tag mice that are predisposed to prostate cancer due to the directed expression of SV40 oncogenes combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While the majority of preclinical studies have found similar beneficial effects of regular physical activity and/or ET on tumor growth in several cancer types, 49 inconsistencies remain. In PCa more specifically, regular exercise was reported to slow tumor growth in five different studies, [21][22][23][24]26 this effect being borderline significant in one other study, 25 while it did not decrease tumor volume in three other ones. 27,29,50 McCullough et al even observed a faster tumor growth in immunodeficient rats after 5 weeks of treadmill running in comparison to their sedentary counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the majority of preclinical studies have found similar beneficial effects of regular physical activity and/or ET on tumor growth in several cancer types, 49 inconsistencies remain. In PCa more specifically, regular exercise was reported to slow tumor growth in five different studies, [21][22][23][24]26 this effect being borderline significant in one other study, 25 while it did not decrease tumor volume in three other ones. 27,29,50 McCullough et al even observed a faster tumor growth in immunodeficient rats after 5 weeks of treadmill running in comparison to their sedentary counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bonn et al found that walking or cycling a minimum of 20 minutes per day was associated with a 30% decrease in overall mortality rates . In vivo, six studies have reported that exercise could significantly or border‐line significantly decrease the prostate tumor growth, while three others however did not find any effect …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This important finding reflects the mounting observational evidence suggesting exercise training can reduce the rate of prostate tumour progression [33]. Greater insights can be gathered from preclinical trials [34][35][36][37][38][39]. Rundqvist and colleagues [40] harvested LNCaP cells with exercise serum (drawn after 60 min of incremental cycling exercise) and reported a growth inhibitory effect (31%), which persisted 96 h post-exercise.…”
Section: The Potential Impact Of Exercise On Tumour Growth?mentioning
confidence: 95%